(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This study aims to clarify areas of using information technology in accounting and its impact on the profession of auditors by reviewing the concept, types, areas and the importance of information technology and its implications on the audit profession as well as to clarify the extent of contribution of information technology in developing of procedures of the audit profession and what its requirement, also this study aims to enhance the theoretical side by identifying the views of a sample of auditors in Arab countries selected (Iraq, Syria, Jordan), for the extent of using of information technology in their work and level of their perception for the importance of that